Effect of Metformin on Testosterone Levels in Male Patients With Type 2 Diabetes Mellitus Treated With Insulin - Cai, Tingting; Hu, Yun; Ding, Bo; Yan, Rengna; Liu, Bingli; Cai, Ling; Jing, Ting; Jiang, Lanlan; Xie, Xiaojing; Wang, Yuming; Wang, Huiying; Zhou, Yunting; et al. (Frontiers in Endocrinology, 2021)
Aim: To explore the chronic effects of metformin on testosterone levels in men with type 2 diabetes mellitus (T2DM). Methods: This is a secondary analysis of a real-world study evaluating the efficacy and safety of premixed insulin treatment in patients with T2DM via 3-month intermittent flash glucose monitoring. Male patients aged 18-60 who were using metformin during the 3-month study period were included as the metformin group. The control group included males without metformin therapy by propensity score matching analysis with age as a covariate. Testosterone levels were measured at baseline and after 3-month treatment. Results: After 3-month treatment, the control group had higher levels of total testosterone, free and bioavailable testosterone than those at baseline (P＜0.05). Compared with the control group, the change of total (-0.82±0.59 vs. 0.99±0.59 nmol/L) and bioavailable (-0.13±0.16 vs. 0.36±0.16 nmol/L) testosterone levels in the metformin group significantly decreased (P=0.037 and 0.029, respectively). In Glycated Albumin (GA) improved subgroup, the TT, FT and Bio-T levels in the control subgroup were higher than their baseline levels (P < 0.05). Compared with the metformin subgroup, TT level in the control subgroup also increased significantly (P=0.044). In GA unimproved subgroup, the change of TT level in the metformin subgroup was significantly lower than that in the control subgroup (P=0.040). Conclusion: In men with T2DM, 3-month metformin therapy can reduce testosterone levels, and counteract the testosterone elevation that accompanied with the improvement of blood glucose. This trial is registered with ClinicalTrials.gov NCT 04847219.